Characterization of a new plastic scintillation material and comparison with liquid BC-501A scintillator - Poleshchuk, Oleksii (2015)
In this work the capability of various scintillation materials to discriminate gamma rays and neutrons were studied. Also such basic properties of scintillators as light emission spectrum and light output were determined. The studied materials were BC-501A liquid scintillator and a plastic scintillator provided by CEA. An experimental setup consisting of detector shielding, analog and digital electronics and data acquisition system was built to study the neutron-gamma discrimination properties of the scintillation materials. Pulse shape discrimination (PSD) technique was utilized. A computer code with a PSD algorithm was written. This code integrates the scintillation pulse waveforms over suitable time ranges for discrimination. Radioactive sources of Na-22, Co-60 and Cs-137 were used to examine the light output from the scintillation material. The neutron-gamma discrimination properties were studied with Cf-252 source. Liquid scintillator shows better discrimination capability than the studied plastic detector.